Dentin hypersensitivity: a challenge in dental practice - Mogrovejo Angulo , Fiorela Isabel (2021)
Dentine hypersensitivity is defined as short, sharp pain from exposed dentin in reaction to thermal, evaporative, tactile, osmotic, or chemical stimuli. This condition is associated with non-carious cervical lesions (erosion, abrasion and abfraction), gingival recessions, periodontal disease, among other dental problems. Due to its multifactorial nature, the diagnosis of dentin hypersensitivity is often difficult and confusing for the dental surgeon. There is no single strategy that can solve this condition in all patients and it is the responsibility of the dental surgeon to know its characteristics in order to propose an effective treatment plan for patients. Therefore, this review aims to show the main characteristics of dentin hypersensitivity, as well as the challenges associated with clinical management, for understanding and mastery in clinical practice.